Access to information as a tool of the prevention of corruption in EU institutions - Korać Srđan (Međunarodni Problemi)
The author analyses the impact of exercising the right to access to information and respecting of transparency for the prevention of corruption in the EU institutions. These two issues are the key principles of good governance and basic prerequisites for democratic participation, allowing citizens to effectively protect their fundamental rights and liberties through public scrutiny. The EU standards are assessed by comparison with the internationally recognized standards, and five indicators have been used: the scope of the right to access, the scope of exceptions, the administrative and appeal procedure, the protection of whistleblowers, administration performance openness and political will. The author wonders if the adopted regulations and rules of procedure are strict enough to prevent emergence of corruption and maladministration in the EU institutions.